Predileksi dan Perubahan Patologi Anatomi pada Ikan Maskoki (Carassius auratus) akibat Infestasi Lernaea cyprinacea Di Kabupaten Tulungagung [Predilection and Anatomical Pathology Changes in Goldfish (Carassius auratus) Due to Lernaea Cyprinacea Infestation in Tulungagung] - Kismiyati Kismiyati; Nadia Ayu Fadila Asshaufi; Hari Suprapto (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
Abstract Goldfish (Carassius auratus) is one of the most popular freshwater fish, therefore they has a very great potential market. Increased effort in Goldfish (Carassius auratus) aquaculture industry, fish farmer also faced greater problems. One of it is disease caused by ectoparacites Lernaea cyprinacea. The predilection of Lernaea cyprinacea can be be directly visible, by the presence of parasites attached to the body surface, fins, gills, eyes and mouth of fish. Lernaea cyprinacea attack on fish can cause pathological change such as lesions and nodules on the skin and fins. This research was conducted in March-November 2013. Location of sampling conducted in Tulungagung East Java while Goldfish (Carassius auratus) pathological examination in the Laboratory of Faculty of Fisheries and Marine Airlangga University. The purpose of this study was to determine the predilection of Lernaea cyprinacea that mostly infested on Goldfish (Carassius auratus) and knowing the change of anatomical pathology in Goldfish (Carassius auratus) infested by Lernaea cyprinacea. The method used was a survey method with random sampling technique and change in anatomic pathology described by the scoring method. The result showed that the predilection of Lernaea cyprinacea mostly infested on Goldfish (Carassius auratus) on dorsal and caudal fin, anatomic pathology changes on Goldfish (Carassius auratus) that infested by Lernaea cyprinacea are abscess, haemorhage, laceration, and fins damaged